2014
DOI: 10.3389/fnagi.2014.00101
|View full text |Cite
|
Sign up to set email alerts
|

Impairment of Vocal Expression of Negative Emotions in Patients with Alzheimer’s Disease

Abstract: Vocal expression of emotions (EE) in retrieval of events from autobiographical memory was investigated in patients in early stages of Alzheimer’s disease (AD). Twenty-one AD patients and 19 controls were interviewed, and EE of the reported memories was rated by 8 independent evaluators. The AD group had lower EE of both recent and remote memory than controls, although EE in remote memories was better preserved in both groups. We observed positive correlations between EE and indicators of cognitive competence i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
1
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 33 publications
0
9
1
2
Order By: Relevance
“…pitch) abilities contribute to prosodic processing more generally, it also offers a more general proof-of-concept for a new approach to the cognitive neuroscience of neuropsychiatric illnesses.Illnesses like schizophrenia are increasingly appreciated as being heterogeneous innature,and abnormal behavior such as prosody perception may be impaired in some individuals, but not in others. Additionally, many of the socio-cognitive markers such as impaired prosody perception that present in schizophrenia are not specific to the illness, and alsopresent in other disorders such as autism, Alzheimer"s disease, bipolar disorder, and Parkinson"s disease (42)(43)(44)(45)(46). From a neuroscience perspective, the ability to perceive social intent through prosody is a highly complex event involvingmany cortical and subcortical brain regions (47)(48)(49)(50).…”
Section: Discussionmentioning
confidence: 99%
“…pitch) abilities contribute to prosodic processing more generally, it also offers a more general proof-of-concept for a new approach to the cognitive neuroscience of neuropsychiatric illnesses.Illnesses like schizophrenia are increasingly appreciated as being heterogeneous innature,and abnormal behavior such as prosody perception may be impaired in some individuals, but not in others. Additionally, many of the socio-cognitive markers such as impaired prosody perception that present in schizophrenia are not specific to the illness, and alsopresent in other disorders such as autism, Alzheimer"s disease, bipolar disorder, and Parkinson"s disease (42)(43)(44)(45)(46). From a neuroscience perspective, the ability to perceive social intent through prosody is a highly complex event involvingmany cortical and subcortical brain regions (47)(48)(49)(50).…”
Section: Discussionmentioning
confidence: 99%
“…Alzheimer's disease (AD), a global health problem with a high prevalence rate, has been recognized as a neurodegenerative disease characterized by progressive cognitive impairment (e.g., memory loss) and neuropsychiatric symptoms (e.g., impairment of vocal expression of emotions) during aging (Han et al, ). Owing to the growth of the aging population, the incidences of AD and other dementias are increasing rapidly.…”
Section: Some Clock‐related Diseasesmentioning
confidence: 99%
“…In AD, a few studies reported reduced expression of emotions, 18 , 19 and this reduction correlated with cognitive impairment across multiple domains, including memory and attention. 18 While no study exists for DLB, reports on emotional expression alterations in Parkinson's disease (PD), another form of the Lewy body spectrum disorder, are abundant. 9 Alterations in vocal and facial expressions of emotions in PD are likely attributed to parkinsonian motor impairments, specifically hypokinetic dysarthria and facial bradykinesia, 9 although several studies have also suggested associations with executive dysfunction and alterations in the affective process.…”
Section: Introductionmentioning
confidence: 99%